Scanning Electron Microscopy as a Tool for Castings Quality Analysis - J. Jezierski; M. Dojka; M. Stawarz; R. Dojka (Archives of Foundry Engineering, 2022)
Nowadays, the best castings’ manufacturers have to meet very demanding requirements and specifications applicable to mechanical properties and other characteristics. To fulfill those requirements, more and more sophisticated methods are being used to analyze the internal quality of castings. In many cases, the commonly used Non-Destructive Methods, like X-ray or ultrasonic testing, are not enough to ensure precise and unequivocal evaluation. Especially, when the properties of the casting only slightly fail the specification and the reasons for such failures are very subtle, thus difficult to find without the modern techniques. The paper presents some aspects of such an approach with the use of Scanning Electron Microscopy (SEM) to analyze internal defects that can critically decrease the performance of castings. The paper presents the so-called bifilm defects in ductile and chromium cast iron, near-surface corrosion caused by sulfur, micro-shrinkage located under the risers, lustrous carbon precipitates, and other microstructure features. The method used to find them, the results of their analysis, and the possible causes of the defects are presented. The conclusions prove the SEM is now a powerful tool not only for scientists but it is more and more often present in the R&D departments of the foundries.